A proposed model for Mantle upwelling in the Syrian coastal - Khaddam, Rasha Houssam (Journal of natural sciences, life and applied sciences, 2021)
The aim of the research is to develop a conception of the proposed model for Mantle upwelling (diapering) in the coastal region, as the results of this research showed the occurrence of Mantle upwelling regression under the coastal region during the Pliocene period, and this led to the occurrence of basaltic deposits in the Syrian coast during the Pliocene, where we note the center of the vaulting was under Qardaha and Safita, and the Mantle upwelling reached a depth of 35 km within the continental crust, where basalt rocks were formed as a result of partial melting of the upper mantle, and it is upwelled with low melting and differential degrees. Basalt rocks in the initial differential phase of the original basaltic silage.
Keywords: coat vaulting; model; Syrian coast; basalt rocks